Can the integration of agriculture and tourism improve the rural human settlement environment?—based on panel data of 30 provinces over 2008–2022 in China - Liu, Ziyi; Chen, Chen (Frontiers in Sustainable Food Systems, 2025)
Comprehensively improving the rural human settlement environment is one of the important aspects of rural revitalization in China. Building beautiful and livable villages is of vital importance to the well-being of farmers. Based on the panel data of 30 provinces in China from 2008 to 2022, this study uses the entropy weight TOPSIS model to measure the level of rural human settlement environment (RHSE), and employs the entropy value method, factor analysis method and grey correlation degree model to evaluate the level of agriculture tourism integration (ATL). On this basis, the dynamic spatial Durbin model and threshold effect model are used to test the impact of ATL on RHSE. The results show: ① RHSE and ATL have significant spatial clustering characteristics. Given the dynamic and continuous characteristics of RHSE, the dynamic spatial Durbin model can better reveal the relationship between the two. ② ATL has a significant direct impact and spillover effect on RHSE. That is, agriculture tourism integration can effectively improve the rural human settlement environment. And in the four regions of the east, central, west and northeast, the direct effect in the central region is the strongest, and the spillover effect in the eastern region is the most significant. ③ The impact of ATL on RHSE has a prominent stage and economic dependence, demonstrating typical nonlinear threshold characteristics. The impact effect of ATL on RHSE shows a dual threshold characteristic as the ATL increases, and a single threshold characteristic as the regional economic level improves. Based on above results, this paper pionts that the government should strengthen policy design, implement differentiated agriculture tourism integration paths based on the regional characteristics of the eastern, central, and western regions, and promote the improvement of the rural human settlement environment. Meanwhile, it should establish a cross-regional collaborative governance mechanism and implement the Talent Revitalization Project to enhance the level of agriculture tourism integration and its sustained driving force for environmental improvement.